Antimicrobial Stewardship Improvement in Pediatric Intensive Care Units in Spain-What Have We Learned? - Elena Fresán-Ruiz; Ana Carolina Izurieta-Pacheco; Mònica Girona-Alarcón; Juan Carlos de Carlos-Vicente; Amaya Bustinza-Arriortua; María Slocker-Barrio; Sylvia Belda-Hofheinz; Montserrat Nieto-Moro; Sonia María Uriona-Tuma; Laia Pinós-Tella; Elvira Morteruel-Arizcuren; Cristina Schuffelmann; et al. (MDPI AG, 2022)
Antibiotic misuse in pediatric intensive care units (PICUs) can lead to increased antimicrobial resistance, antibiotic-triggered side effects, hospital costs, and mortality. We performed a multicenter, prospective study, analyzing critically ill pediatric patients (≥1 month to ≤18 years) admitted to 26 Spanish PICUs over a 3-month period each year (1 April-30 June) from 2014-2019. To make comparisons and evaluate the influence of AMS programs on antibiotic use in PICUs, the analysis was divided into two periods: 2014-2016 and 2017-2019 (once 84% of the units had incorporated an AMS program). A total of 11,260 pediatric patients were included. Total antibiotic prescriptions numbered 15,448 and, overall, 8354 patients (74.2%) received at least one antibiotic. Comparing the two periods, an increase was detected in the number of days without antibiotics in patients who received them divided by the number of days in PICUs, for community-acquired infections (p < 0.001) and healthcare-associated infections (HAIs) acquired in PICUs (p < 0.001). Antibiotics were empirical in 7720 infections (85.6%), with an increase in appropriate antibiotic indications during the second period (p < 0.001). The main indication for antibiotic adjustment was de-escalation, increasing in the second period (p = 0.045). Despite the high rate of antibiotic use in PICUs, our results showed a significant increase in appropriate antibiotic use and adjustment following the implementation of AMS programs.